Transient leukemia - Anand Hema; Bakhshi Sameer; Saxena Renu (Wolters Kluwer Medknow Publications, 2009)
A new born with a mongoloid slant, brachycephaly and low-set ears presented at birth with a total leucocyte count of 57 x 10 3 /µL and the differential leucocyte count revealed 70% of these to be blasts. The morphology of the blasts was not characteristic of myeloid and lymphoid lineage. Cytochemistry showed myeloperoxidase (MPO), Sudan Black B (SBB), periodic acid-Schiff (PAS) and non-specific esterase (NSE) negativity. Flowcytometry showed blasts that were positive for CD-33, CD-34 and CD-7. On second follow-up on the 10th day, the same picture persisted on morphology. On subsequent follow-up, the blasts disappeared. This was thus confirmed to be a case with transient leukemia with Downs syndrome.